Different types of mechanical vibration application on EMG response and strength performance - Aler R. Almeida (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aim: The present study aimed to compare the strength performance and the neuromuscular activity during one maximum repetition test (1RM), and the maximum voluntary isometric contractions (MVIC) performed with whole-body vibration (WBV), local vibration (LV), and no vibration (NV). Methods: The sample consisted of 15 males, experienced in strength training for at least 6 months, which performed all strength tests in the barbell curl exercise across randomized trials on the following conditions: NV, WBV, and LV. During all tests, the normalized root means square values of the electromyographic signals (EMGRMS) of the biceps brachii and brachioradialis were recorded and compared between the conditions. The one-way ANOVAs with repeated measures were used to compare the results of 1RM and MVIC tests and the normalized EMGRMS between the conditions. When necessary, a post hoc Scott-Knott test was used to identify the differences reported in the ANOVAs. The significance level adopted was α < 0.05. Results: The EMGRMS response of the biceps brachii and brachioradialis muscles during the 1RM and MVIC tests presented significantly higher values at LV compared to WBV, and NV (p < 0.001). The 1RM tests, and the MVIC results were similar between conditions (p = 0.9803; p = 0.061, respectively). Conclusion: These results indicate that the application of MV was not sufficient to increase strength performance.